Blue Cards, Blue Prospects? - D'Artis Kancs; Pavel Ciaian (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
Recently, the European Commission has proposed to introduce a new mi- gration policy instrument - Blue Cards - to attract highly skilled workers from abroad by lifting labour market restrictions, offering financial and housing ben- efits. The excludability character of human capital suggests that what is benefi- cial for receiving countries might be hfirmful for sending countries. This article investigates if and why high-skill migration in general and Blue Card scheme in particular might be hfirmful for sending countries. We find that the proposed Blue Card scheme makes the developing country growth prospects indeed blue. However, compared to other firms of labour migration, the upcoming Blue Card scheme is known well in advance. Analysing alternative policy options we show that, taking advantage of this ex-ante infirmation, targeted and timed policy interventions can minimise the adverse impacts of high-skill emigration. Thus, compared to other migration regimes Blue Cards are worse for sending countries, but they offer better opportunities for them to avoid the adverse impacts.
Keywords: F02; F22; 330; High-skill migration; innovative capital; economic growth; Brain Drain; Standortwettbewerb; Migrationspolitik; Wirtschaftswachstum; EU-Staaten